2019
DOI: 10.3390/md17070424
|View full text |Cite
|
Sign up to set email alerts
|

Abalone Collagen Extracts Potentiate Stem Cell Properties of Human Epidermal Keratinocytes

Abstract: Stem cell activities in human tissues are critical for tissue integrity and function. Maintaining keratinocyte stem cells (KSCs) stemness helps sustain healthy skin by supporting keratinocyte renewal, involving the formation of epidermal barriers. In this study, abalone collagen (AC) extracts with molecular weights of 3 kDa (AC 1) and 300 kDa (AC 2) were compared to the epidermal growth factor (EGF) for their effects on cell proliferation, cell migration (wound healing), spheroid formation, and the expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…The present study showed that HCSS treatment at the concentrations 100, 500, and 1000 μg/mL significantly enhanced keratin 19 and β-catenin protein expression in keratinocyte HaCaT cells when compared to the untreated control (Figure 6A and Figure 6B). Our results were similar to those from the previous studies reporting that the collagen extract from abalone caused an increase in KSCs marker expression, such as ALDH1A1, keratin 19, and β-catenin in keratinocyte HaCaT cells [Thaweekitphathanaphakdee et al, 2019]. In addition, collagen type I enhanced the properties of stem cell-like phenotype by the α 2 β 1 -integrin activation [Kirkland, 2009].…”
Section: Hcss Increases the Expression Of Stem Cell Markerssupporting
confidence: 92%
See 3 more Smart Citations
“…The present study showed that HCSS treatment at the concentrations 100, 500, and 1000 μg/mL significantly enhanced keratin 19 and β-catenin protein expression in keratinocyte HaCaT cells when compared to the untreated control (Figure 6A and Figure 6B). Our results were similar to those from the previous studies reporting that the collagen extract from abalone caused an increase in KSCs marker expression, such as ALDH1A1, keratin 19, and β-catenin in keratinocyte HaCaT cells [Thaweekitphathanaphakdee et al, 2019]. In addition, collagen type I enhanced the properties of stem cell-like phenotype by the α 2 β 1 -integrin activation [Kirkland, 2009].…”
Section: Hcss Increases the Expression Of Stem Cell Markerssupporting
confidence: 92%
“…Research conducted by Yang et al [2019b] also showed that peptides from Nibea japonica skin collagen increased cell viability of NIH-3T3 fibroblasts. Additionally, abalone collagen was observed to increase keratinocyte viability [Thaweekitphathanaphakdee et al, 2019]. Based on the results, we selected the HCSS concentrations of 50, 100, 500, and 1000 μg/mL for further experiments.…”
Section: Effect Of Hcss On Cell Viability Of Keratinocyte Hacatmentioning
confidence: 99%
See 2 more Smart Citations
“…FN10, a part of the fibronectin type III module, contains RGD sequences that specifically bind αvβ1 to guide the fate of the cells (Bharadwaj et al 2017 ; Hocking et al 1996 ). Moreover, collagen and fibronectin support the growth of human embryonic stem cells (hESC) without the use of a feeder layer under certain conditions (Lu et al 2006 ) and play a role in maintaining the stemness of stem cells (Akhir and Teoh 2020 ; Thaweekitphathanaphakdee et al 2019 ). Notably, as the main strain matrix element, collagen relies on fibronectin, fibronectin-bound, and collagen-bound integrins to complete its corresponding functions (Kadler et al 2008 ; Kubow et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%